Analysis Of The Art Education Curriculum Islamic-Based Universities In The Performing Art Education Study Program - Chandra Diana Islamanov; Yudi Sukmayadi (Edumaspul: Jurnal Pendidikan, 2024)
The curriculum is the life of a learning program so that its existence requires dynamic design, implementation and evaluation in accordance with the times, the needs of Science, Technology and Art (IPTEKS) and the competencies needed by society, as well as users of higher education graduates. Higher Education as a producer of educated human resources needs to measure its graduates, whether the graduates produced have the ability to be equivalent to the ability of learning outcomes that have been formulated at the Indonesian National Qualifications Framework (KKNI) level. The purpose of this research is to analyze the curriculum policy study built by UMTAS on the Sendratasik Education Study Program based on Islamic Universities. This research uses a qualitative research approach with analytical descriptive methods. The main subjects of this research are stakeholders in the UMTAS Sendratasik Education Study Program who are also the main sources. Data collection was taken from observation, interviews and document analysis related to the problem. The findings of this study are the UMTAS Sendratasik Education Study Program curriculum planning policy is carried out by: a) Preparation of the vision and mission of the study program which refers to the vision and mission of UMTAS; b) Determination of graduate profiles in accordance with the needs of stake holders.